2021
DOI: 10.3390/microorganisms9020410
|View full text |Cite
|
Sign up to set email alerts
|

Agroecological Service Crops Drive Plant Mycorrhization in Organic Horticultural Systems

Abstract: Mycorrhizal symbiosis represents a valuable tool for increasing plant nutrient uptake, affecting system biodiversity, ecosystem services and productivity. Introduction of agroecological service crops (ASCs) in cropping systems may determine changes in weed community, that can affect the development of the mycorrhizal mycelial network in the rhizosphere, favoring or depressing the cash crop mycorrhization. Two no-till Mediterranean organic horticultural systems were considered: one located in central Italy, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Although Glomeromycota phylum was not relevant in terms of relative abundance (Figure 8), the coexistence of rhizosphere microbial communities under cabbage-beetroot IC apparently reduced the strong inhibiting effect played by cabbage on mycorrhizal fungi population at AU site. The presence of weeds species with supporting arbuscular mycorrhizal trait, such as Capsella bursapastoris L., Senecio vulgaris L., Spergula arvensis L., and Plantago maior L. (results not shown), recorded in beetroot IC only, evidently promoted the beetroot mycorrhization (Figure 4B), overruling the inhibiting effect played by the nonmycorrhizal cabbage (Hajiboland et al, 2020;Trinchera et al, 2021). This finding underpinned the hypothesis that different species of plant in the field play a selection of rhizosphere microbiome according to the plant functional traits: here, by promoting the migration of beneficial fungi population toward the beetroot (Trinchera et al, 2016).…”
Section: Crop Root Mycorrhizationmentioning
confidence: 94%
See 1 more Smart Citation
“…Although Glomeromycota phylum was not relevant in terms of relative abundance (Figure 8), the coexistence of rhizosphere microbial communities under cabbage-beetroot IC apparently reduced the strong inhibiting effect played by cabbage on mycorrhizal fungi population at AU site. The presence of weeds species with supporting arbuscular mycorrhizal trait, such as Capsella bursapastoris L., Senecio vulgaris L., Spergula arvensis L., and Plantago maior L. (results not shown), recorded in beetroot IC only, evidently promoted the beetroot mycorrhization (Figure 4B), overruling the inhibiting effect played by the nonmycorrhizal cabbage (Hajiboland et al, 2020;Trinchera et al, 2021). This finding underpinned the hypothesis that different species of plant in the field play a selection of rhizosphere microbiome according to the plant functional traits: here, by promoting the migration of beneficial fungi population toward the beetroot (Trinchera et al, 2016).…”
Section: Crop Root Mycorrhizationmentioning
confidence: 94%
“…In fact, a positive effect of legume–cereal crop rotations on beneficial fungi (e.g., mycorrhizae) was found under Mediterranean conditions, being strongly correlated to SOC, and to occurrence and β-diversity of arbuscular mycorrhiza fungi genera (Pellegrino et al, 2020 ). In addition, crop diversification (e.g., IC, living mulch, and cover crops) seems to promote the beneficial plant–fungi symbiotic association (Trinchera et al, 2019 , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A general point of view relates the between AMF and plants as different ecological strategies indicating functional groups form based on ecosystem conditions. The previous study has shown differences in the composition of the AMF community, for example, found in grasslands, vegetable crops, trees, forests or in certain plant species [36,[40][41][42][43].…”
Section: Abundance and Diversity Of Amf In Different Elevationsmentioning
confidence: 99%
“…The current agroecological approach attributes an important role to AM-host weeds, or spontaneous flora, in designing sustainable and performing agroecosystems [ 9 , 10 , 11 ]. Simard et al (2012) [ 12 ] found that different forest species are able to develop a belowground common mycorrhizal mycelial network (MMN), which implies also material transfer, such as organic C, nutrients, water, defense signals, and allelochemicals among AM plants.…”
Section: Introductionmentioning
confidence: 99%